2001
DOI: 10.1021/ac000987n
|View full text |Cite
|
Sign up to set email alerts
|

Concepts and Preliminary Observations on the Triple-Dimensional Analysis of Complex Volatile Samples by Using GC×GC−TOFMS

Abstract: The high-resolution two-dimensional comprehensive gas chromatography (GC×GC) separation of a complex sample of an essential oil is reported, with tentative identification of selected separated components provided by time-offlight mass spectrometry (TOFMS). The GC×GC technique allows orthogonal separation mechanisms on the two columns to achieve separation of components that otherwise are unresolved on a single column, as is demonstrated for the pairs of components borneol and terpinen-4-ol, and cis-caryophylle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(80 citation statements)
references
References 33 publications
0
80
0
Order By: Relevance
“…GCxGC-ToFMS technology has been shown to provide high-quality mass spectra with great sensitivity, largely as a result of the enhanced resolution and zone compression obtained from the orthogonal separation (Shellie et al, 2001). These qualities were exemplified by the 5-to 10-fold increase in the signal-to-noise ratio of a series of commonly emitted volatiles that we compared with the results from one-dimensional analyses performed with the same instrument (data not shown).…”
Section: Nontargeted Functional Analysis Of Gcxgc-tofms Datamentioning
confidence: 99%
“…GCxGC-ToFMS technology has been shown to provide high-quality mass spectra with great sensitivity, largely as a result of the enhanced resolution and zone compression obtained from the orthogonal separation (Shellie et al, 2001). These qualities were exemplified by the 5-to 10-fold increase in the signal-to-noise ratio of a series of commonly emitted volatiles that we compared with the results from one-dimensional analyses performed with the same instrument (data not shown).…”
Section: Nontargeted Functional Analysis Of Gcxgc-tofms Datamentioning
confidence: 99%
“…Sensitivity and limits of detection are improved due to focusing of the peak in the modulator and separation of analytes from chemical background [8] compared to 1D-GC. ToFMS (time-of-flight mass spectrometry) brings several advantages such as full mass spectra acquisition at trace level sensitivity and mass spectral continuity, which allows for deconvolution of spectra of co-eluted peaks [9]. To the best of our knowledge, GC × GC-ToFMS methodology has never been reported before to study allergic asthma exhaled breath volatile composition.…”
Section: Introductionmentioning
confidence: 99%
“…The principles, practical and theoretical aspects, and the most significant developments of GC×GC were reviewed by Mondello et al (2008). There are several reports of GCxGC used for determining essential oils (Dimandja et al, 2000;Shellie et al, 2003;Shellie et al, 2001). …”
Section: Two-dimensional Gcmentioning
confidence: 99%
“…The high resolution GC×GC separation of an essential oil and the identification of selected separated components by time-of-flight mass spectrometry (TOF-MS) was reported by Shellie et al, (2001). These authors showed that GC×GC allows orthogonal separation mechanisms on the two columns to achieve separation of components (e.g.…”
Section: Two-dimensional Gcmentioning
confidence: 99%